Agromorphological diversity and structuring of lima bean (Phaseolus lunatus L.) accessions from the National Germplasm Collection of INIA Peru - Ventura Neyra, Cristhian Jesus (2026)
Background. Lima bean (Phaseolus lunatus L.) is a key crop for food security along the Peruvian coast due to its high nutritional value and tolerance to drought and heat. However, the agromorphological variability of its national germplasm had not been characterized comprehensively or across multiple years. Objective. To characterize the agromorphological diversity over multiple years and identify phenotypic groups among 35 accessions of the National Lima Bean Germplasm Collection (INIA–Peru). Methodology. Thirty-six descriptors (17 qualitative and 19 quantitative) were used to characterize agromorphology across three consecutive growing seasons (2021, 2022, and 2023). A factorial analysis of mixed data (FAMD) was applied, followed by hierarchical clustering, estimation of Shannon and Pielou diversity indices, mean comparisons, and Pearson correlations. Results. Four phenotypic groups were identified, mainly defined by traits related to earliness and productivity. The Shannon (H′ = 1.05) and Pielou (J′ = 0.95) indices revealed high diversity in pod and seed traits. Quantitative variables, except leaflet length, differed significantly among groups (p < 0.01), and strong correlations were found among earliness traits (r > 0.87) and among yield components (r = 0.74–0.84). Implications. This research provides key information to support conservation strategies and the use of lima bean germplasm in genetic improvement programs in Peru and other similar agroecological regions. Conclusions. The National Lima Bean Germplasm Collection of INIA exhibits a broad and structured phenotypic diversity organized into four groups, supported by nine qualitative and eighteen quantitative discriminant descriptors.